Feeding habit of blue swimming crab (Portunus pelagicus) in Kawal Waters, Bintan Regency - Loisa Yolanda; Wahyu Muzammil; Susiana Susiana (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
Kawal Waters is one of the waters in Bintan which has good fishery resources, one of that is the blue swimming crab. The Blue Swimming Crab (Portunus pelagicus) is one of the important economic fisheries resources belonging to the Portunidae family. The blue swimming crab is one of the most common organisms used by the community. The purpose of the study was to determine food composition of blue swimming crab (Portunus pelagicus) in Kawal waters of Bintan Island, Riau Island on June 2021. The sampling used random sampling method. There were 34 individuals used for food composition analysis. The food composition in the stomach of blue swimming crab consisted of three groups of microalgae, crustacea, and detritus. The food composition in the adult size was found microalgae groups with the percentage composition 78%. It was followed by crustacea of 18,06%, and detritus of 5,12%. The highest of indeks of stomatch contens is in morning caught of 1,15 for males and 1,28 for female.